2010
DOI: 10.5507/fot.2010.004
|View full text |Cite
|
Sign up to set email alerts
|

Silica-scaled Chrysophyceae and Synurophyceae from Nigeria III. Chrysophytes from rivers of Edo State.

Abstract: A total of 18 species of silica-scaled chrysophytes (Chrysophyceae: one species each in Chrysosphaerella, Spiniferomonas, and Paraphysomonas; Synurophyceae: 11 Mallomonas spp. and four Synura spp.) was recorded from river samples collected in Edo State, Benin, Nigeria, from both dry and rainy seasons in 2003. Identifications were based on transmission electron microscopy. Five are new records for Nigeria, including four being newly reported for Africa. Two further species could not be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Therein, the chrysophytes were found in water reservoirs with similar temperatures (between 22-29 °C in Lake Kariba, around 30 °C in two other ponds in Zimbabwe- Cronberg & Hickel 1985, Cronberg 1988b, 1989bbetween 26-33 °C in Lekki Lagoon, Nigeria-Wujek et al 2003-200429.5 °C in small pond in Cameroon-Piątek et al 2012), pH (between 7.26-8.15 in Lake Kariba, Zimbabwe-Cronberg 1989bbetween 6.1-7.7 in Lekki Lagoon, Nigeria-Wujek et al 2003-20047.8 in small pond in Cameroon- Piątek et al 2012), with similar (35 µS•cm -1 in small pond in Cameroon- Piątek et al 2012), but usually with much higher electrolytic conductivity (640-1230 µS•cm -1 in Lake Kariba, Zimbabwe-Cronberg 1989b; 200-1000 µS•cm -1 in Lekki Lagoon, Nigeria- Wujek et al 2003Wujek et al -2004. Interestingly, similar environmental conditions (pH between 5.8-6.8, conductivity between 12-82 µS•cm -1 ) were detected in several Nigerian rivers that have diverse assemblages of chrysophyte species (Wujek et al 2010). In general, Cronberg (1989b) concluded that chrysophytes in the tropics (including Afrotropics) are more frequent in small water reservoirs than in large lakes, and the present observation in Cameroon is also from a small lake.…”
Section: Introductionsupporting
confidence: 72%
“…Therein, the chrysophytes were found in water reservoirs with similar temperatures (between 22-29 °C in Lake Kariba, around 30 °C in two other ponds in Zimbabwe- Cronberg & Hickel 1985, Cronberg 1988b, 1989bbetween 26-33 °C in Lekki Lagoon, Nigeria-Wujek et al 2003-200429.5 °C in small pond in Cameroon-Piątek et al 2012), pH (between 7.26-8.15 in Lake Kariba, Zimbabwe-Cronberg 1989bbetween 6.1-7.7 in Lekki Lagoon, Nigeria-Wujek et al 2003-20047.8 in small pond in Cameroon- Piątek et al 2012), with similar (35 µS•cm -1 in small pond in Cameroon- Piątek et al 2012), but usually with much higher electrolytic conductivity (640-1230 µS•cm -1 in Lake Kariba, Zimbabwe-Cronberg 1989b; 200-1000 µS•cm -1 in Lekki Lagoon, Nigeria- Wujek et al 2003Wujek et al -2004. Interestingly, similar environmental conditions (pH between 5.8-6.8, conductivity between 12-82 µS•cm -1 ) were detected in several Nigerian rivers that have diverse assemblages of chrysophyte species (Wujek et al 2010). In general, Cronberg (1989b) concluded that chrysophytes in the tropics (including Afrotropics) are more frequent in small water reservoirs than in large lakes, and the present observation in Cameroon is also from a small lake.…”
Section: Introductionsupporting
confidence: 72%
“…Mallomonas acaroides was found in mountainous areas of Zimbabwe [34] and the tropics and subtropics of China [66,67]. Mallomonas parvula is found in the tropics and subtropics of China [66], Nigeria [68,69], and Ecuador [70]. Mallomonas pseudocratis was reported in India [27] and the tropics and subtropics of China [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, this species was the most frequently reported taxon in both eutrophic and hypereutrophic water bodies, which are prevalent in the studied area of Northern Vietnam. Generally, Mallomonas kenyana has a scattered distribution and is restricted to tropical and subtropical areas in North and South America [34,78,79], Africa [68,69,80,81], and Asia [26,27,29,66].…”
Section: Discussionmentioning
confidence: 99%
“…Chrysosphaerella annulata has been found in Vietnam, in Dong Nai province [124]. It is a widespread species in the tropical region [54,55,57,59,68,69,100,125] and has been noted in the temperate zone [126].…”
Section: Discussionmentioning
confidence: 99%